PERANCANGAN FURNITUR BERBAHAN ROTAN DAN FASILITAS PENDUKUNGNYA - Palupi, Andita Eka; P. Utomo, Tri Novianto; Nuradhi, L. Maureen (KREASI, 2017)
Pal’S Gallery is a furniture design business that will be open in Surabaya, East Java. The showroom location will be in the 2nd floor of Marvell City Mall, Raya Ngagel 123, Wonokromo, Surabaya City, East Java. Pal’S Gallery specialize in furniture design and furniture product using rattan as the main materials. The purpose of this business are to fulfill the market demand for furnitures, and to enrich the Indonesia design with its uniqe rattan furniture design. Pal’S Gallery will serve customer with furniture design service and also selling the finished or ready-to-use furniture products. This research covered the design research, concept, and implementation report of the furniture, product, and its display space. Pal’S Gallery’s display space are consist of showroom and exhibition booth. The division area showroom and booth are less the same, there are public areas and private areas. Area divider of diplay space base on the showroom and booth existing. The existing area of showroom itself has 90 m2 total area. While, the booth has several alternatives design base on the booth size and type, there are the booth with a size of 3x3m surrounded with three backdrop in three different sides, the booth with a size of 3x3m surrounded with two backdrop in two different sides, the booth with a size of 3x6m surrounded with a backdrop in the 6m sides, and the island booth with a size of 6x6m. The concept for Pal’s Gallery display will be use rattan materials designed in a modern space planning and enclosure shape.